PERCEPTION OF WOMEN ON THE CAUSES AND EFFECTS OF INDOOR AIR POLLUTION IN KANO METROPOLIS - Darda, F. O.; Ogunleye, A. O.; Hassan, M. T. (FUDMA JOURNAL OF SCIENCES, 2023)
This paper assessed the perception of women on the causes and effects of indoor air pollution in Kano metropolis, Nigeria. Two local government areas within the metropolis were used for the study. Questionnaires were used to generate responses which were then analyzed. The result of the research showed that 82% of respondents have basic education that will furnish them with basic knowledge on issues about environmental pollution. Inadequate ventilation and overcrowdings are the most predisposing factors to increasing air pollution in the home. Smoke generated from burning fuel, dust and pesticides (52%, 18% and 13% respectively) top the list of indoor air pollutants. Many women even though aware of the occurrence of indoor air pollutants, the health effects of indoor air pollution are poorly understood. It is therefore recommended that women should be continuously enlighten and educated on the causes and effects of indoor air pollution so that they realize the dangers and health hazards of living in polluted environment and take charge of their own health and that of the family.